2015
DOI: 10.1111/liv.12897
|View full text |Cite
|
Sign up to set email alerts
|

HCV‐associated B‐cell non‐Hodgkin lymphomas and new direct antiviral agents

Abstract: Direct anti-viral agents might be proposed as a first-line treatment in marginal zone lymphomas in the case of no life-threatening complications with the precaution of a long-term follow-up. In the setting of diffuse large B-cell lymphomas, well-tolerated direct anti-viral agents could potentially be introduced very early not only to prevent relapse of these lymphomas but also to limit the liver toxicity of chemotherapy and rituximab by preventing outbreaks of viral load. New observations and trials should sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 18 publications
2
50
2
3
Order By: Relevance
“…To date, 3 published cases have reported successful antiviral treatment in HCV-associated DLBCL using sofosbuvir-based regimens. Carrier et al [5] reported 2 patients who developed SVR with a sofosbuvir-daclatsvir antiviral regimen, but treatment of HCV-infection was initiated only after clinical remission of the lymphoma was declared. Likewise, Romagnoli et al [6] achieved SVR in an HCV-infected patient in remission from DLBCL using sofosbuvir, ribavirin, and IFN.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 3 published cases have reported successful antiviral treatment in HCV-associated DLBCL using sofosbuvir-based regimens. Carrier et al [5] reported 2 patients who developed SVR with a sofosbuvir-daclatsvir antiviral regimen, but treatment of HCV-infection was initiated only after clinical remission of the lymphoma was declared. Likewise, Romagnoli et al [6] achieved SVR in an HCV-infected patient in remission from DLBCL using sofosbuvir, ribavirin, and IFN.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few data to assess how DAAs will affect clinical outcome in patients with extrahepatic manifestations of chronic hepatitis C 57. While it is clear that the presence of mixed cryoglobulinaemia was a predictive factor of poor response to IFN-based therapy,58 to what extent the use of DAAs may change treatment outcomes in this group of patients deserves further study.…”
Section: Introductionmentioning
confidence: 99%
“…Five patients were already reported in the literature [10][11][12] and were included with updated follow-up. Approval for this study, which was based on the use of archival or cohort data, was obtained from the Institutional Review Boards of the participating centers.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…However, data on the efficacy of IFN-free regimens 10 in HCVassociated lymphoproliferative disorders are scanty and based on clinical reports. 11,12 In this study, we have evaluated the virological and lymphoproliferative disease response (LDR) rates and toxicity of DAAs in a large series of patients with indolent lymphoproliferative disorders treated by DAAs in the absence of immunochemotherapy.…”
Section: Introductionmentioning
confidence: 99%